Monocyte Adhesion, Migration, and Extracellular Matrix Breakdown Are Regulated by Integrin αVβ3 in Mycobacterium tuberculosis Infection - Brilha, Sara; Wysoczanski, Riccardo; Whittington, Ashley M; Friedland, Jon S; Porter, Joanna C (The Journal of immunology (1950), 2017)
In tuberculosis (TB), the innate inflammatory immune response drives tissue destruction, morbidity, and mortality. Monocytes secrete matrix metalloproteinases (MMPs), which have key roles in local tissue destruction and cavitation. We hypothesized that integrin signaling might regulate monocyte MMP secretion in pulmonary TB during cell adhesion to the extracellular matrix (ECM). Adhesion to type I collagen and fibronectin by Mycobacterium tuberculosis–stimulated monocytes increased MMP-1 gene expression by 2.6-fold and 4.3-fold respectively, and secretion by 60% (from 1208.1 ± 186 to 1934.4 ± 135 pg/ml; p < 0.0001) and 63% (1970.3 ± 95 pg/ml; p < 0.001). MMP-10 secretion increased by 90% with binding to type I collagen and 55% with fibronectin, whereas MMP-7 increased 57% with collagen. The ECM did not affect the secretion of tissue inhibitors of metalloproteinases-1 or -2. Integrin αVβ3 surface expression was specifically upregulated in stimulated monocytes and was further increased after adhesion to type I collagen. Binding of either β3 or αV integrin subunits increased MMP-1/10 secretion in M. tuberculosis–stimulated monocytes. In a cohort of TB patients, significantly increased integrin β3 mRNA accumulation in induced sputum was detected, to our knowledge, for the first time, compared with control subjects (p < 0.05). Integrin αVβ3 colocalized with areas of increased and functionally active MMP-1 on infected monocytes, and αVβ3 blockade markedly decreased type I collagen breakdown, and impaired both monocyte adhesion and leukocyte migration in a transwell system (p < 0.0001). In summary, our data demonstrate that M. tuberculosis stimulation upregulates integrin αVβ3 expression on monocytes, which upregulates secretion of MMP-1 and -10 on adhesion to the ECM. This leads to increased monocyte recruitment and collagenase activity, which will drive inflammatory tissue damage.